INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM NOVEL SOEDIRMAN & ALFIAH : KISAH-KISAH ROMANTIS JENDERAL SOEDIRMAN DAN ALFIAH KARYA E. ROKAJAT ASURA: Internalisasi, Nilai, Pendidikan Islam, Novel - Maulana, Maulana (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
The purpose of this study was to identify the content of Islamic educational values contained in the novel. Because Islamic education values are very important to be instilled in order to have an understanding of Islamic education, diverse learning resources are growing rapidly following the current development of the times, so that it becomes a new challenge for Islamic education. Novels are one of the alternative learning resources that are full of the values of Islamic education. In order to find out the value of Islamic education contained in them, a qualitative approach method is used through library research. The results obtained in the novel Soedirman & Alfiah: The Romantic Stories of General Soedirman and Alfiah by E. Rokajat Asura are the educational values of Worship, Akidah and Akhlak.